Effectiveness and Safety of Newer Antidiabetic Medications for Ramadan Fasting Diabetic Patients - Mudher Mikhael, Ehab (J Diabetes Res, 2016)
Hypoglycemia is the most common side effects for most glucose-lowering therapies. It constitutes a serious risk that faces diabetic patients who fast during Ramadan (the 9th month in the Islamic calendar). New glucose-lowering classes like dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like peptide 1 receptor agonist (GLP-1 RA), and sodium-glucose cotransporter-2 (SGLT-2) inhibitors are efficacious in controlling blood glucose level with less tendency to induce hypoglycemia and thus may constitute a good choice for diabetic patients during Ramadan. This study reviews the safety and efficacy of newer glucose-lowering therapies during Ramadan. This study was accomplished through a careful literature search about studies that assess the benefit and side effects of these new glucose-lowering therapies during Ramadan during September 2015. Vildagliptin, sitagliptin, liraglutide, exenatide, and dapagliflozin were the only studied glucose-lowering therapies. All of the studied newer glucose-lowering therapies except dapagliflozin were associated with reduced risk to induce hypoglycemia. Gastrointestinal upset was common with the usage of liraglutide while increased thirst sensation was common with dapagliflozin. In conclusion DPP-4 inhibitors such as vildagliptin and sitagliptin may form a suitable glucose-lowering therapy option for Ramadan fasting patients.